-9=u/3+-6

Simple and best practice solution for -9=u/3+-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9=u/3+-6 equation:



-9=u/3+-6
We move all terms to the left:
-9-(u/3+-6)=0
We add all the numbers together, and all the variables
-(u/3-6)-9=0
We get rid of parentheses
-u/3+6-9=0
We multiply all the terms by the denominator
-u+6*3-9*3=0
We add all the numbers together, and all the variables
-1u-9=0
We move all terms containing u to the left, all other terms to the right
-u=9
u=9/-1
u=-9

See similar equations:

| 11(x+7)=5(6x-8)-6x | | 9k-(-3k-7)=15 | | (6x+20)+(2x+4)=0 | | 49=x−48 | | 0.07g-6.5=0.2g | | 2x+56=4x-14 | | 3x-12=6x+5 | | -5x20=100 | | 7p+5p-3p=21+9-10 | | 7a−3=13a+7 | | -4+33=2x+81 | | -6(h+7)+8=-19 | | (6+6x)=-22x+2 | | -26=-10+8k | | (5u+10)=5 | | 4≤x+2≤=8 | | -10n-35=0 | | 8n-(4n+5)=9 | | -3=x-1-3 | | 11+21=-4(6x-8) | | (4n+19)-(6(n-9))=0 | | 83=21+m | | 8(y+2)+2y=-34 | | 5(x-5)=4(x+8) | | 2-6x-2=12 | | 2n+54-19=0 | | 8x-12=-71 | | 4=-2(1-3x)-6(x-1) | | 2+3(x1)=17 | | 1/5*(x-3)=3/4 | | -12=-2(r+5) | | -5/8v=20 |

Equations solver categories